Islamic Educational Institution Infrastructure Management Al-Quran An-Nahl, Al-Maidah, Al-Ghosiyah, Al-Mujadalah - Lazuardi Lazuardi; Muhammad Yusuf Pulungan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Infrastructure in learning is an infrastructure and also a facility that supports the process in an educational institution that must be managed and managed properly, because it is necessary to use, use, provide and good planning so as to bring a benefit to educational institutions, without any infrastructure. The learning process will be difficult. The type of method used is maudhui (thematic) interpretation which collects verses of the Qur'an with the aim of discussing one theme As stated in surah An- Nahl verse 68-69 mapping the concept of building with the division of labor, sura Al - Ghosiyah verse 12-21 regarding the future that must be considered, surah Al- Maidah verse 31 regarding dependence on one another so that it cannot be stand alone without other and complement each other and surah Al- Mujilah verse 11 about the high degree of a person who seeks knowledge.